PM.17 Impact of Maternal Obesity on Accuracy of Sonographic Fetal Weight Estimation in IUGR. (26th April 2013) - Cody, F; Unterscheider, J; Daly, S; Geary, MP; Kennelly, MM; McAuliffe, FM; O'Donoghue, K; Hunter, A; Morrison, JJ; Burke, G; Dicker, P; Tully, EC; et al.
Abstract : Objective: The objective of this analysis, as part of the multicentre prospective PORTO Trial, was to determine whether increasing maternal BMI decreases the accuracy of sonographic fetal weight estimation in IUGR pregnancies. Study design: The PORTO Trial recruited 1, 118 consecutive ultrasound-dated singleton IUGR pregnancies, defined as EFW < 10 th centile. Maternal BMI was recorded at booking and divided into 4 subcategories. Accuracy of fetal weight assessment was defined as difference between EFW within 2 weeks of delivery and actual birthweight. Results: Of the 1, 076 recruited patients with complete records, 693 (64%) were of normal weight (BMI < 25), 258 (24%) were overweight (BMI 25–30), 93 (9%) were obese class I (BMI 30–35) and 32 (3%) were obese class II (BMI 35–40) (Table 1 ). Overall, fetal weight estimation prior to delivery was within 6% of respective birthweight. EFW was not influenced by increasing maternal BMI and EFW accuracy was only marginally better in normal weight mothers. Greater BMI was associated with earlier gestational age at delivery. Conclusion: These data show that ultrasound is reliable in the assessment of fetal weight in IUGR in the presence of increased maternal BMI.